Odpowiedź :
a)12x-(2x+1)=9(2-x)
12x-2x-1=18-9x
12x-2x+9x=18+1
19x=19 /:19
x=1
L=12*1-(2*1+1) = 12-(2+1)=12-3=9
P=9*(2-1)=9*1=9
b)3(x+1)-4=2(x-2)+2x
3x+3-4=2x-4+2x
3x-2x-2x=-4-3+4
-x=-3 /*(-1)
x=3
L = 3*(3+1)-4 = 3*4-4 = 12-4 = 8
P = 2*(3-2)+2*3 = 2*1+6 = 2+6 = 8
12x-2x-1=18-9x
12x-2x+9x=18+1
19x=19 /:19
x=1
L=12*1-(2*1+1) = 12-(2+1)=12-3=9
P=9*(2-1)=9*1=9
b)3(x+1)-4=2(x-2)+2x
3x+3-4=2x-4+2x
3x-2x-2x=-4-3+4
-x=-3 /*(-1)
x=3
L = 3*(3+1)-4 = 3*4-4 = 12-4 = 8
P = 2*(3-2)+2*3 = 2*1+6 = 2+6 = 8
a) 12x-(2x+1)=9(2-x)
12x-2x-1=18-9x
10x-1=18-9x
9x=9x ,czyli strony sa sobie równe.
b)3(x+1)-4=2(x-2)+2x
3x+3=2x-4+2x
6x=6x strony także sa sobie równe
na 100 % dobrze rozwiązane:):)
12x-2x-1=18-9x
10x-1=18-9x
9x=9x ,czyli strony sa sobie równe.
b)3(x+1)-4=2(x-2)+2x
3x+3=2x-4+2x
6x=6x strony także sa sobie równe
na 100 % dobrze rozwiązane:):)